Peran Media Sosial Instagram Sebagai Media Promosi Pada Coffee Shop Kopi Kita Padang Dalam Meningkatkan Brand Awareness - metari Alhamdaniyah; zike Martha (CV. ITTC INDONESIA, 2025)
Coffee shop businesses are growing rapidly in Padang City. This can be seen from the increasing number of coffee shops, both small and large scale. Kopi Kita, a local coffee shop targeting the youth market, uses Instagram as its main promotional medium. This shop seeks to build relationships with consumers through visual content such as product photos, customer reviews, and discount promotions and special events. The purpose of this study is to analyze the effectiveness of using Instagram social media as a promotional medium in increasing brand awareness. The theory used in this study is the Hierarchy of Effects Model Theory. The research method used is descriptive qualitative, used to collect data related to promotional activities on Instagram, engagement, and the impact on consumer behavior. The data used in this study were obtained from in- depth interviews with predetermined informants. The data in this study were tested using data source triangulation. Based on the results of the study regarding the process of forming brand awareness through several stages: awareness, interest, desire and action. Instagram plays a role in facilitating brand awareness through attractive visual content and special promos and interactions with customers. From this stage, it can be seen that Toko Kopi Kita has successfully implemented the hierarchy of effects model theory, as evidenced by the increasing number of visitors to Kopi Kita. Based on the data obtained from the research results on the role of Instagram social media as a promotional media at Kopi Kita coffee shop in increasing brand awareness, it can be concluded that Instagram social media is very effective as a promotional media to increase Kopi Kita brand awareness, and visual, educational and interactive content is the most effective promotional strategy. The use of relevant hashtags and interacting with customers increases brand awareness and Instagram plays an important role in building brand image and increasing Kopi Kita sales.